A Note on the Górnicki-Proinov Type Contraction. (28th January 2021) - Karapınar, Erdal; De La Sen, Manuel; Fulga, Andreea
Abstract : In this paper, we propose a notion of the Górnicki-Proinov type contraction. Then, we prove the uniqueness and existence of the fixed point for such mappings in the framework of the complete metric spaces. Some illustrative examples are also expressed to strengthen the observed results.